The effect of inquiry-based teaching on students' attitudes toward science as an academic subject as well as science and technology in general - Ganajová, Mária; Orosová, Renáta; Sotáková, Ivana; Letošnı́ková, Petra (Frontiers in Education, 2025)
IntroductionThe research aim was to identify the impact of IBSE in teaching science subjects (biology, physics, and chemistry) on students' attitudes to these subjects, as well as science and technology in general.MethodsThe systematic literature review, conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, involved an analysis of systematic reviews and empirical studies published between 2015 and 2025. The qualitative meta-analysis focused on the implementation of IBSE in STEM education, examining its effectiveness and impact on students' attitudes toward science subjects, the perceived difficulty and usefulness of these subjects, trust in science, the perceived societal contribution of science and technology, and students' career ambitions in this field. The empirical part of this study presents research conducted with first-year students from five Slovak grammar schools over a 3-month period (November to January) during the 2022/2023 school year. A one-group pre-test–post-test design was used. The research sample consisted of 151 students. The intervention comprised 24 lessons and included 12 inquiry-based activities designed according to the 5E model (Engage, Explore, Explain, Elaborate, Evaluate). These activities were implemented in teaching three science subjects—physics, chemistry, and biology. A scale questionnaire developed within the ESTABLISH project was used to assess students' attitudes toward science subjects, as well as science and technology, before and after the intervention.ResultsAfter completing the inquiry-based activities, students' attitudes toward science subjects increased significantly across all five subscales. They reported stronger emotional engagement with science subjects (Subscale A; strong effect) and perceived them as less difficult and more useful (Subscale B; strong effect). With regard to science and technology, students expressed greater appreciation of their societal relevance (Subscale C; strong effect), demonstrated increased trust and fewer critical reservations toward scientific knowledge and processes (Subscale D; medium effect), and showed stronger professional aspirations within the field of science and technology (Subscale E; medium to strong effect).DiscussionTo enhance students' understanding of the importance of science and technology, additional tasks focusing on STEM and global challenges such as digitalization, climate change, and artificial intelligence should be incorporated into inquiry-based activities.